The short term musculoskeletal and cognitive effects of prolonged sitting during office computer work - Baker, R.; Coenen, P.; Howie, E.; Williamson, A.; Straker, Leon (Molecular Diversity Preservation International (MDPI), 2018)
Office workers are exposed to high levels of sedentary time. In addition to cardio-vascular and metabolic health risks, this sedentary time may have musculoskeletal and/or cognitive impacts on office workers. Participants (n = 20) undertook two hours of laboratory-based sitting computer work to investigate changes in discomfort and cognitive function (sustained attention and problem solving), along with muscle fatigue, movement and mental state. Over time, discomfort increased in all body areas (total body IRR [95% confidence interval]: 1.43 [1.33–1.53]) reaching clinically meaningful levels in the low back and hip/thigh/buttock areas. Creative problem solving errors increased (ß = 0.25 [0.03–1.47]) while sustained attention did not change. There was no change in erector spinae, trapezius, rectus femoris, biceps femoris and external oblique median frequency or amplitude; low back angle changed towards less lordosis, pelvis movement increased, and mental state deteriorated. There were no substantial correlations between discomfort and cognitive function. The observed changes suggest prolonged sitting may have consequences for musculoskeletal discomfort and cognitive function and breaks to interrupt prolonged sitting are recommended.